Influence of Catalase and Superoxide Dismutase on Ozone Inactivation of Listeria monocytogenes - Fisher, Christopher W. (American Society for Microbiology, 2000)
The effects of ozone at 0.25, 0.40, and 1.00 ppm on Listeria monocytogenes were evaluated in distilled water and phosphate-buffered saline. Differences in sensitivity to ozone were found to exist among the six strains examined. Greater cell death was found following exposure at lower temperatures. Early stationary-phase cells were less sensitive to ozone than mid-exponential- and late stationary-phase cells. Ozonation at 1.00 ppm of cabbage inoculated with L. monocytogenes effectively inactivated all cells after 5 min. The abilities of in vivo catalase and superoxide dismutase to protect the cells from ozone were also examined. Three listerial test strains were inactivated rapidly upon exposure to ozone. Both catalase and superoxide dismutase were found to protect listerial cells from ozone attack, with superoxide dismutase being more important than catalase in this protection.